NARAPIDANA PEREMPUAN DALAM PENJARA ( SUATU KAJIAN ANTROPOLOGI GENDER ) - Sumarauw, Yunitri (Universitas Sam Ratulangi, 2013)
The development and progress of the world today seems increasingly complex with a wide range of human behavior or action . Patterns of thought and action which is expressed not only in the form of patterns of thought or action action ''positive'', however , there is also a form of ''negative'' actions that harm others or themselves. Negative ''action'' is usually called the crime. There is also the negative behavior can be attributed to violations of social norms, religion, or government regulations. Usually the government's violation of the rules will enter into the category of crime . This paper is a preliminary picture of the Life of Women In Prison Class II Manado , which requires further research . This paper is also expected to be a reference to a student majoring in Anthropology Fisp Unsrat to the study of the lives of women in prison.Keyword : Convict women , gender anthropology